1994
DOI: 10.1159/000282580
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Nifedipine on Stone Formation and Renal Function in Cholesterol-Induced Nephrolithiasis in Rats

Abstract: Previous investigations showed that nifedipine limited calcium phosphate stone formation induced by a high-cholesterol diet in rats. This study was performed to obtain further insights into the effects of nifedipine on stone prevention, renal function and urine composition. Male Wistar rats were assigned to one of the following groups: (1) cholesterol diet (n = 22), (2) cholesterol diet plus nifedipine (n = 22) and (3) control (n = 6). A high-cholesterol diet was given for 4 weeks, nifedipine was administered … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…In Japan, detailed cross-sectional studies on the presence or absence of insulin resistance were performed, and they determined that female patients with kidney stones had high insulin resistance and insulin values, supporting the link between obesity and urolithiasis (21). Furthermore, one study reports that urolithiasis formation (calcium phosphate) is observed in the kidney when rats receive a high cholesterol diet (22).…”
Section: Discussionmentioning
confidence: 96%
“…In Japan, detailed cross-sectional studies on the presence or absence of insulin resistance were performed, and they determined that female patients with kidney stones had high insulin resistance and insulin values, supporting the link between obesity and urolithiasis (21). Furthermore, one study reports that urolithiasis formation (calcium phosphate) is observed in the kidney when rats receive a high cholesterol diet (22).…”
Section: Discussionmentioning
confidence: 96%
“…Alterations in calcium metabolism at the cellular level have been described in patients with arterial hypertension [14]. In experimental studies, similar mechanisms could be shown to play a role in the pathogenesis of stone formation [15, 16]. Since urolithiasis is a common disease (prevalence in industrialized nations 4%), the new onset of hypertension in those patients has a strong socioeconomic impact.…”
Section: Discussionmentioning
confidence: 99%